Composite positive electrode for rate-type solid-state battery, preparation method and battery
By adopting a composite cathode preparation method in solid-state batteries, using dehydrofluoride pretreatment and cross-linkable multi-olefinic ether-containing monomers to form a three-dimensional cross-linked conductive network, the rate of existence of high-nickel ternary cathode materials during the cycle is solved. To overcome the problems of poor performance and capacity fading, it achieves better rate and cycle performance and better interface contact.
Patent Information
- Application Number
- CN202411749618.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The high-nickel ternary cathode materials in existing solid-state batteries have problems with cation mixing and oxygen release on the electrode surface during the cycle, resulting in poor rate performance and capacity attenuation, and poor interface affecting electrochemical performance.
The composite positive preparation method is used for a multiplier -type solid -state battery. It is treated with a hydrogenation of solid electrolytic pulp and fluoride polymers, and the cross -linked polymethlert bond containing ether mono is added to the high nickel ternary positive material. Body, forming a uniform and dense three -dimensional joint conduction network.
It achieves uniform surface coating and good interface contact of the composite cathode, improves the rate and cycle performance of the battery, and suppresses the structural degradation and electrochemical performance attenuation of high-nickel ternary cathode materials.
Smart Images

Figure CN119230758B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for preparing a composite positive electrode for a rate-type solid-state battery, a composite positive electrode prepared thereby, and a rate-type solid-state battery composed of the composite positive electrode. Background Art
[0002] Lithium-ion batteries have been widely used in consumer electronics such as laptops and mobile phones, and have gradually become the mainstream energy storage solution for electric vehicles to reduce carbon dioxide emissions and energy consumption. With the continuous pursuit of energy density and safety, solid-state batteries have gradually attracted attention as an emerging energy storage technology, and are highly anticipated for their potential high energy density and better safety.
[0003] Solid-state batteries usually use high-nickel ternary cathode materials to further improve energy density. However, despite the high specific capacity of high-nickel ternary cathode materials, they still face problems such as cation mixing and oxygen release on the electrode surface during the cycle, resulting in poor rate performance and rapid capacity decay during the cycle. At the same time, the interface problem between the cathode and the solid electrolyte in solid-state batteries cannot be ignored. Poor interface will lead to Li + The transfer impedance of ions at the interface between the electrode and the electrolyte increases, thus affecting the overall electrochemical performance. In addition, there is a large amount of lithium slag (such as Li2O and LiOH) on the surface of the positive electrode material. These impurities accelerate the decomposition of the electrolyte to produce hydrogen fluoride, further aggravating the interface instability.
[0004] In the prior art, strategies for solving the problems of high-nickel ternary layered materials and improving their electrochemical performance mainly include surface coating, element doping, single crystal structure and concentration gradient design, etc. Among them, surface coating is one of the effective strategies to improve the thermal stability and structural stability of high-nickel ternary positive electrode materials. Through this method, a protective layer can be formed on the surface of the electrode material, which has many beneficial effects on the electrode material, including improving the ionic conductivity of the positive electrode material, promoting electron transfer and lithium ion diffusion, stabilizing the surface structure, preventing the positive electrode material from directly contacting the electrolyte, and preventing gas precipitation.
[0005] At present, various coating routes developed based on surface coating include mechanical mixing, sol-gel, pulsed layer deposition (PLD), chemical vapor deposition (CVD) and atomic layer deposition (ALD). When these methods are applied, the coating of high-nickel ternary positive electrode materials is uneven, the interface contact is not ideal, and the process is complex, time-consuming and costly, which is not conducive to continuous mass production.
[0006] Based on this, how to use a simple process flow to achieve uniform surface coating of the positive electrode material in solid-state batteries, solve its interface contact problem, and improve the battery rate and cycle performance is an issue that we urgently need to solve. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a composite positive electrode for a rate-type solid-state battery, which has a simple process, short time consumption and low cost, and the composite positive electrode prepared by the method has better rate and cycle performance, more uniform surface coating and better interface contact. At the same time, based on the method for preparing a composite positive electrode for a rate-type solid-state battery, the present invention also provides a composite positive electrode prepared by the method and a rate-type solid-state battery composed of the composite positive electrode.
[0008] The first aspect of the present invention provides a method for preparing a composite positive electrode for a rate-type solid-state battery, which comprises the following steps:
[0009] S1: selecting a solid electrolyte slurry with Lewis alkalinity for dehydration treatment, and obtaining a dehydrated solid electrolyte slurry after standing;
[0010] S2: adding 1-5 wt% of a fluorine-containing polymer to the dehydrated solid electrolyte slurry, heating the slurry at 40-75° C. to cause the fluorine-containing polymer to undergo a dehydrofluorination reaction under Lewis alkaline conditions, heating for 1-6 hours to complete the dehydrofluorination reaction of the fluorine-containing polymer, and then stopping heating to obtain a mixed solution;
[0011] S3 subjecting the mixed solution to ultrasonic stirring treatment, so that the surface of the solid electrolyte is evenly covered with the dehydrofluorinated fluorinated polymer containing C=C active sites, to obtain a dehydrofluorinated surface-coated solid electrolyte slurry;
[0012] S4: selecting a positive electrode slurry, adding 1-5 wt% of a cross-linkable polyene-ether-containing monomer, and performing high-speed stirring and vacuum defoaming treatment to form a layer of a cross-linkable polyene-ether-containing monomer on the surface of the positive electrode active material of the positive electrode slurry to obtain a surface cross-linkable pretreated positive electrode slurry;
[0013] S5: adding 2-5 wt% of the dehydrofluorinated surface-coated solid electrolyte slurry to the surface cross-linkable pretreated positive electrode slurry, stirring at a high temperature of 40-50° C. to promote the cross-linkable polyene-bond ether-containing monomer to cross-link with the C=C active site on the surface of the solid electrolyte to form a cross-linked network structure, thereby obtaining a composite positive electrode slurry with a solid electrolyte uniformly coated on the surface;
[0014] S6: coating and cutting the composite positive electrode slurry to obtain the composite positive electrode.
[0015] In the preparation method, the fluorine-containing polymer includes the following molecular structure:
[0016]
[0017] Wherein, R1 and R2 are groups having electron-withdrawing effect or groups having conjugated structure or -H or -CH3; H represents hydrogen element, F represents fluorine element, and n represents the degree of polymerization.
[0018] In the preparation method, the fluorine-containing polymer is one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer or a combination of the two.
[0019] In the preparation method, the solid electrolyte slurry is prepared from one or a combination of any two or more of the following: garnet-type solid electrolyte, perovskite-type solid electrolyte, and NASICON-structured solid electrolyte.
[0020] In the preparation method, the cross-linkable multi-olefinic ether-containing monomer is a monomer compound containing multiple olefinic bonds and ether groups.
[0021] In the preparation method, the cross-linkable polyolefinic ether-containing monomer is one of ethoxylated tripropylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, and trimethylolpropane triallyl ether, or a combination of any two or more thereof.
[0022] In the preparation method, the positive electrode slurry is specifically prepared in the following manner:
[0023] The positive electrode active material, the conductive agent and the binder are selected in a mass ratio of 90-105:1-3:1-3 and mixed and stirred at high speed to prepare the product.
[0024] In the preparation method, the positive electrode active material is a high-nickel ternary positive electrode material;
[0025] The molecular formula of the high nickel ternary positive electrode material is LiNi x Co y Mn z O2, where x+y+z=1, and 0.8≤x≤0.95.
[0026] A second aspect of the present invention provides a composite positive electrode for a rate-type solid-state battery, which is prepared by the above-mentioned preparation method.
[0027] The third aspect of the present invention provides a rate-type solid-state battery, which is prepared by a positive electrode plate, a negative electrode plate and a solid electrolyte layer. The positive electrode plate is prepared by the above-mentioned preparation method, or the positive electrode plate adopts the above-mentioned composite positive electrode; the solid electrolyte slurry in the positive electrode plate and the solid electrolyte layer both use the same solid electrolyte.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention adds a solid electrolyte slurry to a fluorine-containing polymer for dehydrofluorination pretreatment, and adds a cross-linkable polyene-bonded ether-containing monomer to a high-nickel ternary positive electrode material. After the two are mixed evenly, the raw materials are mixed, stirred and coated to finally obtain a uniformly coated composite positive electrode. The entire process is simple, time-saving, and the raw materials used are easy to obtain. The overall process cost is low, and it is suitable for large-scale industrial promotion and application.
[0030] 2. The present invention utilizes cross-linkable polyolefin-containing ether monomers to undergo cross-linking reaction with C=C active sites on the surface of solid electrolytes. Through simple stirring and high-temperature treatment, a three-dimensional cross-linked conductive network is formed between the positive electrode active material and the solid electrolyte, effectively connecting the solid electrolyte with the positive electrode active material to form a uniform and dense coating effect, thereby achieving the goal of suppressing the electrochemical performance attenuation and safety issues caused by structural degradation during the charge and discharge process of high-nickel ternary positive electrode materials.
[0031] 2. The present invention has a layer of solid electrolyte uniformly and densely coated on the surface of the composite positive electrode. According to the high ionic conductivity characteristics of the solid electrolyte and the three-dimensional conductive network formed by cross-linking the C=C active sites of the fluorinated polymer molecular chain after dehydrofluorination and the cross-linkable polyene bond ether-containing monomer, the composite positive electrode prepared by the present invention has more lithium ion transmission channels during high current charge and discharge, thereby making the solid-state lithium battery made of the composite positive electrode have better rate performance.
[0032] 3. The present invention utilizes the dehydrofluorination reaction characteristics of fluorinated polymers in a Lewis alkaline environment, adds a fluorinated polymer with dehydrofluorination into the oxide solid electrolyte slurry, and uniformly coats a layer of dehydrofluorinated fluorinated polymer containing C=C active sites on the surface of the solid electrolyte, so that when it is subsequently cross-linked with the positive electrode slurry, a uniform and dense solid electrolyte can be formed on the surface of the high-nickel ternary positive electrode.
[0033] 4. The composite positive electrode prepared by the present invention is assembled to form a solid-state lithium battery. Since the solid electrolyte used in the composite positive electrode is consistent with that used in the solid electrolyte layer, after being assembled into a solid-state battery, the solid electrolyte with the same composition can ensure better interface contact, reduce interface impedance, and improve ion conductivity, thereby achieving the technical effect of optimizing the interface contact problem. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0035] Figure 1 This is a schematic diagram of the composite positive electrode structure of the present invention;
[0036] Figure 2This is an enlarged structural diagram of the surface of the positive electrode active material in the composite positive electrode of the present invention;
[0037] Figure 3 The results of rate tests of solid-state batteries prepared in Specific Example 1, Specific Example 2 and Comparative Example;
[0038] Figure 4 The long cycle test results of the solid-state batteries prepared in Specific Example 1, Specific Example 2 and the comparative example.
[0039] The numbers in the figure represent:
[0040] 1. Composite positive electrode plate;
[0041] 11. positive electrode active material; 12. solid electrolyte; 13. a cross-linked network structure formed by a cross-linking reaction between a cross-linkable polyene-bond ether-containing monomer and a C=C active site on the surface of the solid electrolyte; 14. aluminum foil. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0043] like Figure 1 , Figure 2 As shown, the first embodiment of the present invention provides a method for preparing a composite positive electrode for a rate-type solid-state battery, which comprises the following steps:
[0044] S1: Selecting a solid electrolyte slurry with Lewis alkalinity for dehydration treatment, and obtaining a dehydrated solid electrolyte slurry after standing.
[0045] In this step, the solid electrolyte slurry is selected to have Lewis alkaline properties in order to facilitate the subsequent dehydrofluorination reaction of the fluorine-containing polymer in an alkaline environment and to uniformly coat the surface of the solid electrolyte with a layer of C=C active sites for the subsequent positive electrode material coating reaction.
[0046] In the implementation process, the solid electrolyte slurry is prepared from one or a combination of any two or more of garnet-type solid electrolyte (LLZO), perovskite-type solid electrolyte (LLTO), and NASICON structure solid electrolyte (LATP).
[0047] S2: adding 1-5 wt% of a fluorine-containing polymer to the dehydrated solid electrolyte slurry, heating the slurry at 40-75° C. to cause the fluorine-containing polymer to undergo a dehydrofluorination reaction under Lewis alkaline conditions, heating for 1-6 h to complete the dehydrofluorination reaction of the fluorine-containing polymer, and then stopping heating to obtain a mixed solution.
[0048] In this step, in order to facilitate the dehydrofluorination reaction of the fluorinated polymer under Lewis alkaline conditions, the fluorinated polymer has adjacent CF and CH bonds, which makes it easy for the bimolecular elimination reaction to occur and form partial double bonds on the molecular chain. Specifically, the fluorinated polymer has the following molecular structure:
[0049]
[0050] Wherein, R1 and R2 are groups having electron-withdrawing effect or groups having conjugated structure or -H or -CH3; H represents hydrogen element, F represents fluorine element, and n represents the degree of polymerization.
[0051] Specifically, all groups with electron-withdrawing effects can be fluorine, cyano, and ester groups, whose electronic properties and spatial structures will affect the reactivity of the CF bond and enhance its polarity to promote the dehydrofluorination reaction; the group with a conjugated structure can be a group with an ester aromatic ring, an aromatic ring, or a conjugated double bond to stabilize the conjugated intermediate after dehydrofluorination and promote the reaction; -H is a smaller group, which can reduce steric hindrance, make the reaction active center easier to contact the catalyst, and facilitate the dehydrofluorination reaction; and R1 and R2 can also be groups containing active hydrogen atoms such as -CH3, which are prone to β-elimination reaction under alkaline conditions, dehydrofluorination and generate a double bond structure.
[0052] In an implementation process, the fluorine-containing polymer is one or a combination of two substances selected from polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer.
[0053] As a specific implementation manner, the addition amount of the fluorine-containing polymer is 3wt% of the dehydrated solid electrolyte slurry, the heating temperature is 55°C, and the heating time is 3h.
[0054] S3: subjecting the mixed solution to ultrasonic stirring treatment, so that the surface of the solid electrolyte is evenly covered with the dehydrofluorinated fluorinated polymer containing C=C active sites, to obtain a dehydrofluorinated surface-coated solid electrolyte slurry.
[0055] S4: Select positive electrode slurry, add 1-5wt% of cross-linkable polyene ether-containing monomer, and form a layer of cross-linkable polyene ether-containing monomer on the surface of the positive electrode active material of the positive electrode slurry through high-speed stirring and vacuum defoaming treatment to obtain surface cross-linkable pretreated positive electrode slurry.
[0056] In this step, the cross-linkable multi-olefinic ether-containing monomer is a monomer compound containing multiple olefinic bonds (such as double bonds) and ether groups, and can undergo a cross-linking reaction by free radical, photochemical or thermal initiation to form a three-dimensional network structure.
[0057] In the implementation process, the cross-linkable multi-olefin ether-containing monomer is one of ethoxylated tripropylene glycol diacrylate (EO-TPGDA), triethylene glycol diacrylate (TTEGDA), tetraethylene glycol diacrylate (TEGDA), polyethylene glycol diacrylate (PEGDA), trimethylolpropane triallyl ether (TMPTME) or a combination of any two or more thereof.
[0058] As a specific implementation manner, the added amount of the cross-linkable polyolefinic ether-containing monomer is 3 wt % of the positive electrode slurry.
[0059] In the implementation process, the positive electrode slurry is specifically prepared in the following manner:
[0060] The positive electrode active material, the conductive agent and the binder are selected in a mass ratio of 90-105:1-3:1-3 and mixed and stirred at high speed to obtain the product.
[0061] As a specific implementation, the positive electrode slurry is specifically prepared in the following manner:
[0062] The positive electrode active material, conductive agent and binder are selected in a mass ratio of 97:1.8:1.2 and mixed and stirred at high speed to prepare the product.
[0063] In the implementation process, the positive electrode active material is a high-nickel ternary positive electrode material;
[0064] The molecular formula of the high nickel ternary positive electrode material is LiNi x Co y Mn z O2, where x+y+z=1, and 0.8≤x≤0.95.
[0065] S5: 2-5 wt% of the dehydrofluorinated surface-coated solid electrolyte slurry is added to the surface cross-linkable pretreated positive electrode slurry, and stirred at high temperature at 40-50°C to promote the cross-linkable polyene-bonded ether-containing monomer to cross-link with the C=C active site on the surface of the solid electrolyte to form a cross-linked network structure, thereby obtaining a composite positive electrode slurry with a solid electrolyte uniformly coated on the surface.
[0066] As a specific implementation manner, the addition amount of the dehydrofluorinated surface-coated solid electrolyte slurry is 3.5wt% of the surface cross-linkable pretreated positive electrode slurry, and the heating temperature is 45°C.
[0067] S6: coating and cutting the composite positive electrode slurry to obtain the composite positive electrode.
[0068] The composite positive electrode sheet 1 finally prepared is as follows Figure 1 and Figure 2 As shown in the figure, we can see that:
[0069] After being coated on the aluminum foil 14 to form the composite positive electrode, the surface of the positive electrode active material 11 (high nickel ternary positive electrode material) is evenly covered with the solid electrolyte 12. This is because the C=C active sites of the fluorine-containing polymer molecular chains coated on the surface of the solid electrolyte after dehydrofluorination undergo a cross-linking reaction with the cross-linkable polyene-bonded ether-containing monomers on the surface of the positive electrode active material. Through simple stirring and high-temperature treatment, a three-dimensional cross-linked conductive network is formed between the positive electrode active material and the solid electrolyte, that is, a cross-linked network structure 13 is formed by the cross-linking reaction between the cross-linkable polyene-bonded ether-containing monomers and the C=C active sites on the surface of the solid electrolyte. The solid electrolyte is effectively connected to the positive electrode active material to form a uniform and dense coating effect, thereby suppressing the electrochemical performance attenuation and safety problems caused by structural degradation during the charging and discharging process of the high nickel ternary positive electrode material.
[0070] At the same time, the second embodiment of the present invention provides a composite positive electrode for a rate-type solid-state battery based on the first embodiment, which is prepared by the above-mentioned preparation method.
[0071] Finally, the third embodiment of the present invention provides a rate-type solid-state battery based on the first embodiment or the second embodiment, which is prepared by a positive electrode plate, a negative electrode plate and a solid electrolyte layer. The positive electrode plate is prepared by the above-mentioned preparation method, or the positive electrode plate adopts the above-mentioned composite positive electrode; the solid electrolyte slurry in the positive electrode plate and the solid electrolyte layer both use the same solid electrolyte.
[0072] In summary, compared with the existing technology:
[0073] 1. The preparation method described in this embodiment is to add the solid electrolyte slurry to the fluorine-containing polymer for dehydrofluorination pretreatment, and at the same time add a cross-linkable polyene bond ether-containing monomer to the high-nickel ternary positive electrode material, and then mix the two materials and stir and coat them after they are mixed evenly, and finally obtain a uniformly coated composite positive electrode. The whole process is simple, time-saving, and the raw materials used are easy to obtain. The overall process cost is low, which is suitable for large-scale industrial promotion and application.
[0074] 2. The preparation method described in this embodiment utilizes a cross-linkable polyene-bonded ether-containing monomer to undergo a cross-linking reaction with the C=C active site on the surface of the solid electrolyte. Through simple stirring and high-temperature treatment, a three-dimensional cross-linked conductive network is formed between the positive electrode active material and the solid electrolyte, effectively connecting the solid electrolyte with the positive electrode active material. A layer of uniform and dense solid electrolyte can be formed on the surface of the high-nickel ternary positive electrode, forming a uniform and dense coating effect, thereby achieving the goal of suppressing the electrochemical performance attenuation and safety issues caused by structural degradation during the charging and discharging process of the high-nickel ternary positive electrode material.
[0075] 3. The positive electrode plate described in this embodiment has a layer of solid electrolyte uniformly and densely coated on the surface. According to the high ionic conductivity characteristics of the solid electrolyte and the three-dimensional conductive network formed by cross-linking the C=C active sites of the fluorinated polymer molecular chain after dehydrofluorination and the cross-linkable polyene bond ether-containing monomer, it has more lithium ion transmission channels during high current charging and discharging, so that the solid-state lithium battery made of the composite positive electrode has better rate performance.
[0076] 4. The rate-type solid-state battery described in the embodiment of the present invention can form a uniform and dense solid electrolyte structure based on the three-dimensional conductive network of the composite positive electrode structure used therein, forming a uniform and dense coating effect, thereby suppressing the electrochemical performance attenuation and safety problems caused by structural degradation during the charging and discharging process of the high-nickel ternary positive electrode material, so that it has better rate and cycle performance. Moreover, since the solid electrolyte used in the composite positive electrode is consistent with that used in the solid electrolyte layer, after being assembled into a solid-state battery, the solid electrolyte with the same composition can ensure better interface contact, reduce interface impedance, and improve ionic conductivity, thereby achieving the technical effect of optimizing the interface contact problem.
[0077] For better understanding and implementation of the present invention, the present invention is further explained and illustrated in detail below in conjunction with specific embodiments and comparative examples.
[0078] Embodiment 1:
[0079] A method for preparing a composite positive electrode for a rate-type solid-state battery comprises the following steps:
[0080] S1 Select tantalum doped lithium lanthanum zirconium oxide (chemical formula: Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 ) (LLZTO) solid electrolyte slurry, adding molecular sieves to the slurry to remove trace water in the solvent, performing dehydration treatment, and obtaining dehydrated solid electrolyte slurry after standing;
[0081] S2: adding 2 wt % of polyvinylidene fluoride (PVDF) to the dehydrated solid electrolyte slurry, heating at 45° C. to promote dehydrofluorination of polyvinylidene fluoride in the dehydrated solid electrolyte slurry, heating for 2 h to complete the dehydrofluorination of polyvinylidene fluoride, and then stopping heating to obtain a mixed solution;
[0082] S3. subjecting the mixed solution to ultrasonic stirring treatment, so that the surface of the tantalum-doped lithium lanthanum zirconium oxide is evenly covered with the dehydrofluorinated polyvinylidene fluoride containing C=C active sites, to obtain a dehydrofluorinated surface-coated solid electrolyte slurry;
[0083] S4: selecting a positive electrode slurry, adding 3 wt% of tetraethylene glycol diacrylate (TEGDA), and performing high-speed stirring and vacuum defoaming treatment to form a layer of cross-linkable polyolefin-containing ether monomer on the surface of the positive electrode active material of the positive electrode slurry to obtain a surface cross-linkable pretreated positive electrode slurry;
[0084] Among them, the positive electrode slurry is specifically prepared by the following method:
[0085] The positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive agent (conductive carbon black super P), and binder (polyvinylidene fluoride PVDF) are prepared by high-speed mixing and stirring.
[0086] S5: adding 5 wt % of the dehydrofluorinated surface-coated solid electrolyte slurry to the surface cross-linkable pretreated positive electrode slurry, stirring at 45° C. to promote the cross-linkable polyene-bond ether-containing monomer to cross-link with the C=C active site on the surface of the solid electrolyte to form a cross-linked network structure, thereby obtaining a composite positive electrode slurry with a solid electrolyte uniformly coated on the surface;
[0087] S6: coating and cutting the composite positive electrode slurry to obtain the composite positive electrode.
[0088] Based on the composite positive electrode prepared by this preparation method, a solid-state battery A is prepared, specifically:
[0089] The positive electrode in solid-state battery A adopts the composite positive electrode prepared by the preparation method of this embodiment, the negative electrode in solid-state battery A adopts lithium metal, and the solid electrolyte layer solid electrolyte adopts tantalum-doped lithium lanthanum zirconium oxide (LLZTO).
[0090] After the solid-state battery A is prepared, its battery capacity is 10Ah and its energy density is 305Wh / kg.
[0091] Embodiment 2:
[0092] A method for preparing a composite positive electrode for a rate-type solid-state battery comprises the following steps:
[0093] S1 Select lithium aluminum titanium phosphate (chemical formula: Li 1.3 Al 0.3 Ti 1.7 (PO4)3) (LATP) solid electrolyte slurry, adding molecular sieves to the slurry to remove trace water in the solvent, performing dehydration treatment, and obtaining dehydrated solid electrolyte slurry after standing;
[0094] S2: adding 4 wt % of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) to the dehydrated solid electrolyte slurry, heating at 55° C. to promote dehydrofluorination reaction of the polyvinylidene fluoride-hexafluoropropylene copolymer in the dehydrated solid electrolyte slurry, heating for 4 h to complete the dehydrofluorination reaction of the polyvinylidene fluoride-hexafluoropropylene copolymer, and then stopping heating to obtain a mixed solution;
[0095] S3. subjecting the mixed solution to ultrasonic stirring treatment, so that the surface of the lithium titanium aluminum phosphate is evenly covered with the dehydrofluorinated polyvinylidene fluoride-hexafluoropropylene copolymer containing C=C active sites, to obtain a dehydrofluorinated surface-coated solid electrolyte slurry;
[0096] S4: selecting a positive electrode slurry, adding 5 wt% of trimethylolpropane triallyl ether (TMPTME), and performing high-speed stirring and vacuum defoaming treatment to form a layer of cross-linkable polyolefin-containing ether monomer on the surface of the positive electrode active material of the positive electrode slurry to obtain a surface cross-linkable pretreated positive electrode slurry;
[0097] Among them, the positive electrode slurry is specifically prepared by the following method:
[0098] The positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.85 Co 0.1 Mn 0.05 O2), conductive agent (conductive carbon black super P), and binder (polyvinylidene fluoride PVDF) are prepared by high-speed mixing and stirring.
[0099] S5: adding 4 wt % of the dehydrofluorinated surface-coated solid electrolyte slurry to the surface cross-linkable pretreated positive electrode slurry, stirring at 45° C. to promote the cross-linkable polyene-bonded ether-containing monomer to cross-link with the C=C active site on the surface of the solid electrolyte to form a cross-linked network structure, thereby obtaining a composite positive electrode slurry with a solid electrolyte uniformly coated on the surface;
[0100] S6: coating and cutting the composite positive electrode slurry to obtain the composite positive electrode.
[0101] Based on the composite positive electrode prepared by this preparation method, a solid-state battery B is prepared, specifically:
[0102] The positive electrode in solid-state battery B adopts the composite positive electrode prepared by the preparation method of this embodiment, the negative electrode in solid-state battery B adopts a silicon-based negative electrode, and the solid electrolyte layer uses lithium aluminum titanium phosphate (LATP) as the solid electrolyte.
[0103] After the solid-state battery B is prepared, its battery capacity is 10Ah and its energy density is 300Wh / kg.
[0104] Comparative Example 1:
[0105] The positive electrode is prepared by a conventional method, and the specific preparation method is as follows:
[0106] Select the positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive agent (conductive carbon black super P), and binder (polyvinylidene fluoride PVDF) are mixed and stirred at a high speed in a mass ratio of 97:1.8:1.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated and cut to obtain conventional positive electrode sheets.
[0107] Based on the prepared conventional positive electrode sheet, a solid-state battery C is prepared, specifically:
[0108] The positive electrode in the solid-state battery C adopts the conventional positive electrode plate prepared in this comparative example, the negative electrode in the solid-state battery C adopts lithium metal, and the solid electrolyte layer solid electrolyte adopts tantalum-doped lithium lanthanum zirconium oxide LLZTO.
[0109] After the solid-state battery C is prepared, its battery capacity is 10Ah and its energy density is 310Wh / kg.
[0110] The solid-state battery A prepared in Example 1, the solid-state battery B prepared in Example 2, and the solid-state battery C prepared in the comparative example were tested at a rate. They were all charged at a current of 0.5C and discharged at currents of 0.5C, 1C, 2C, 3C, 4C, and 5C, respectively. Each rate charge and discharge cycle was 3 cycles. The test results are as follows: Figure 3 described.
[0111] Combination Figure 3 It can be seen that:
[0112] At low rate discharge (0.5C), solid-state batteries A, B, and C have similar discharge performance, and the capacity retention rates are close to 100%. However, as the discharge current increases, the internal resistance of the battery cell increases, causing the capacity retention rate of the battery cell to gradually decay. Among them, the capacity retention rate of solid-state battery A decays fastest with the increase of discharge current. When the discharge current is 5C, the capacity retention rate decays to 80%, reflecting poor rate performance. At the same time, after the rate test, the battery cell is tested for 0.5C charge and discharge recovery rate, and the capacity retention rate of solid-state battery C is about 98%. This shows that with the increase of discharge current, the positive electrode material of solid-state battery C undergoes irreversible changes, resulting in poor rate discharge and capacity recovery performance. This is due to the instability of high-nickel ternary positive electrode materials and the easy structural degradation under high current.
[0113] On the other hand, solid-state batteries A and B have better rate discharge and capacity recovery performance. When solid-state batteries A and B are discharged at a current of 5C, the capacity retention rate is still 90%, and the recovery rate in the capacity recovery test after the rate is 100%. This shows that the present invention can effectively suppress the capacity degradation of high-nickel ternary under large current by coating the surface of high-nickel ternary positive electrode materials with solid electrolytes, thereby achieving the effect of improving the rate performance of solid-state batteries, and due to the high ionic conductivity of solid electrolytes, the composite positive electrode has more lithium ion transmission channels, so that the rate performance is improved.
[0114] Then solid-state battery A, solid-state battery B, and solid-state battery C were cycled and tested using a 0.5C charge and 3C discharge schedule. The cycle test results are as follows: Figure 4 shown.
[0115] Combination Figure 4 It can be seen that:
[0116] By comparing the cycle data, it can be seen that the solid-state battery C has a cycle dive after 260 cycles, and the battery cell capacity retention rate is less than 80%. This is because the surface of the high-nickel ternary material in the solid-state battery C is not treated, resulting in structural degradation under high current cycles. At the same time, the interface contact between the solid electrolyte and the positive electrode is poor. As the cycle progresses, the interface problem further deteriorates, resulting in the battery cell diving, and the rate and cycle performance are poor. In contrast, solid-state batteries A and B have a cross-linked network structure formed by the cross-linkable polyene-containing ether monomer and the C=C active site on the surface of the solid electrolyte, thereby forming a three-dimensional polymer conductive network between the surface of the high-nickel ternary material and the solid electrolyte, so that the positive electrode surface is coated with a uniform and dense solid electrolyte, avoiding structural degradation of the high-nickel ternary material during the cycle, affecting the cycle performance. At the same time, the conductive network formed by cross-linking makes the composite positive electrode have better conductivity, lower internal resistance of the battery cell, and better cycle performance. In addition, since the solid electrolyte coated on the surface is the same as the solid electrolyte of the solid electrolyte layer, the interface contact between the positive electrode plate and the solid electrolyte layer is good, and the interface contact impedance is lower, so that the cycle performance is improved.
[0117] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a composite positive electrode for a rate-type solid-state battery, characterized in that: It includes the following steps: S1: selecting a solid electrolyte slurry with Lewis alkalinity for dehydration treatment, and obtaining a dehydrated solid electrolyte slurry after standing; S2: adding 1-5 wt% of a fluorine-containing polymer to the dehydrated solid electrolyte slurry, heating the slurry at 40-75° C. to cause the fluorine-containing polymer to undergo a dehydrofluorination reaction under Lewis alkaline conditions, heating for 1-6 hours to complete the dehydrofluorination reaction of the fluorine-containing polymer, and then stopping heating to obtain a mixed solution; S3 subjecting the mixed solution to ultrasonic stirring treatment, so that the surface of the solid electrolyte is evenly covered with the dehydrofluorinated fluorinated polymer containing C=C active sites, to obtain a dehydrofluorinated surface-coated solid electrolyte slurry; S4: selecting a positive electrode slurry, adding 1-5 wt% of a cross-linkable polyene-ether-containing monomer, and performing high-speed stirring and vacuum defoaming treatment to form a layer of a cross-linkable polyene-ether-containing monomer on the surface of the positive electrode active material of the positive electrode slurry to obtain a surface cross-linkable pretreated positive electrode slurry; S5: adding 2-5 wt% of the dehydrofluorinated surface-coated solid electrolyte slurry to the surface cross-linkable pretreated positive electrode slurry, stirring at a high temperature of 40-50° C. to promote the cross-linkable polyene-bond ether-containing monomer to cross-link with the C=C active site on the surface of the solid electrolyte to form a cross-linked network structure, thereby obtaining a composite positive electrode slurry with a solid electrolyte uniformly coated on the surface; S6: coating and cutting the composite positive electrode slurry to obtain the composite positive electrode.
2. The preparation method according to claim 1, characterized in that: The fluorine-containing polymer has the following molecular structure: ; Wherein, R1 and R2 are groups having electron-withdrawing effect or groups having conjugated structure or -H or -CH3; H represents hydrogen element, F represents fluorine element, and n represents the degree of polymerization.
3. The preparation method according to claim 1 or 2, characterized in that: The fluorine-containing polymer is one of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer or a combination of the two.
4. The preparation method according to claim 1, characterized in that: The solid electrolyte slurry is prepared from one or a combination of any two or more of a garnet-type solid electrolyte, a perovskite-type solid electrolyte, and a NASICON-structured solid electrolyte.
5. The preparation method according to claim 1, characterized in that: The cross-linkable multi-olefinic ether-containing monomer is a monomer compound containing multiple olefinic bonds and ether groups.
6. The preparation method according to claim 1 or 5, characterized in that: The cross-linkable polyolefinic ether-containing monomer is one of ethoxylated tripropylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, and trimethylolpropane triallyl ether, or a combination of any two or more thereof.
7. The preparation method according to claim 1, characterized in that: The positive electrode slurry is specifically prepared in the following manner: The positive electrode active material, the conductive agent and the binder are selected in a mass ratio of 90-105:1-3:1-3 and mixed and stirred at high speed to obtain the product.
8. The preparation method according to claim 7, characterized in that: The positive electrode active material is a high-nickel ternary positive electrode material; The molecular formula of the high nickel ternary positive electrode material is LiNi x Co y Mn z O2, where x+y+z=1, and 0.8≤x≤0.
95.
9. A composite positive electrode for a rate-type solid-state battery, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A rate-type solid-state battery, which is prepared from a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, characterized in that: The positive electrode sheet is prepared by the preparation method according to any one of claims 1 to 8, or the positive electrode sheet is the composite positive electrode according to claim 9; The solid electrolyte slurry in the positive electrode plate and the solid electrolyte layer both use the same solid electrolyte.
Citation Information
Patent Citations
Composite solid electrolyte positive electrode piece as well as preparation method and application thereof
CN110176576A
Composite positive electrode material, composite positive electrode plate, all-solid-state battery and preparation method
CN117936789A